(3OjhGf GdaMGes - (3GdaMGe , UGOb Hf eMeO Hf GdMSf Hf gGTe GdMSjfj GdGYQLj, CHh GdfLGIs ((3eMeO Hf GdTjN WGgQ GdSeGhj s)
(3ChdgG (B:s
(3CeG HYO ajbhd gPG eG SeMJ Hg GdbQjMI GdLGeOI ef bUGFO hebWYGJ GTJed Ydi eOGFM fHhjI, hbUGFO YdhjI, heQGKj MSfjjI hQJHJg Ydi KdGKI CHhGH(B: s
(3BNQgG (B:s
(3jhSa HUHQg Ydi GdHdhi dSDdg CbVGg hGddg HGdedc ef HYO GdSLf dg bVGg Je HMeO Gddg GdHGH GdKGdK s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B316s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B174 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHIBjI Gddg GdMcje GdYGeI HGdfLa (B(389) s
Keywords: (3GdCOHs